Hydroecological investigations on the hyporheic zone to support river management from reaches to catchments - Magliozzi, Chiara (Cranfield University, 2018)
The hyporheic zone (HZ) is an area of interaction between surface and ground waters in riverbeds. It is characterized by a diverse fauna and by a bidirectional flow (hyporheic exchange flow - HEF). HZ plays a signifi cant role in river ecosystems as location of major physical, biogeochemical and ecological processes. Yet, predicting HEF in rivers and assessing its ecological effects is challenging due to physical and biological process- interactions in time and space. This thesis investigates HEF from a hierarchical scaling perspective and it has two components: (i) physical, and (ii) biological. The fi rst component includes discriminating and integrating the drivers of HEF across spatial scales and developing a multiscale statistical method for river restoration planning. The second component consists of testing the interaction between physical and biological processes on in-channel large wood (LW), by quantifying, in the field, the effects on hyporheic and benthic invertebrates assemblages taxonomic structure and functional traits. The multiscale approach shows that suitable areas for HEF-focused restoration embed a summary of environmental information across the domains of hydrology, geomorphology, and ecology. Field results about invertebrates' taxonomic and functional metrics, demonstrate that the increased spatial and temporal variability of abiotic conditions at LW sites drives changes in abundance, biomass, diversity and functional traits of hyporheic meiofaunal assemblages. In contrast, benthic macrofaunal assemblages were less wood-impacted. To support restoration targeting the HZ, this research emphasizes the need to (i) recognize different spatial scales of HEF to identify the underlying processes; (ii) coordinate approaches to pool hyporheic data and create long-term datasets to quantitatively assess model predictions; and (iii) establish further knowledge on how LW effects HZ in different valleys and river types.
Keywords: hyporheic zone; multiscale; functional traits; large wood; invertebrates; taxonomy